Longitudinal magnetoresistance of uniaxially deformed n-type silicon - Bigozha, O.D.; Seitmuratov, A.Zh.; Taimuratova, L.U.; Kazbekova, B.K.; Aimaganbetova, Z.K. (Karagandy University of the name of acad. E.A. Buketov, 2022)
The study of Galvano-magnetic effects (as well as tensoeffects) in silicon under extreme conditions allows not only to identify the mechanisms of these effects but also to identify the possibility of creating gaussmeters, infrared detectors, sensitive strain gauges, amplifiers and generators of a wide frequency range. The reliability of the mechanism of negative magnetoresistance was verified using uniaxial elastic deformation of the studied crystals. Uniaxial deformation excludes interline transitions of electrons, as a result of which negative magnetoresistance disappears with an increase in uniaxial pressure. When cubic symmetry is violated, anisotropic phenomena occur in such crystals. The multipath of the isoenergetic surface of the bottom of the silicon conduction band causes anisotropies of the effective mass and relaxation time, which are associated with the features of the transfer phenomenon. In particular, magnetoresistance (piezoresistance), which is the most sensitive to the anisotropy of the iso energy surface. The influence of the latter on magnetoresistance is most clearly revealed in the region of strong magnetic fields, where the magnetoresistance is saturated since the longitudinal magnetoresistance is entirely due to the anisotropy of electron mobility.
Деформацияланған бір осьті n-типтес кремнийдің бойлық магниттіккедергісі
Продольное магнитосопротивление односно-деформированного кремния n-типа
Keywords: galvano-magnetic effects; piezoresistance; negative magnetoresistance; uniaxial pressure; isoenergetic; multivalley model; valley crossing; silicon magnetoresistance